Modelo de programación matemática para la cadena productiva del biodiesel en Colombia - Aranda Pinilla, Johan Alexander; Barón Molina, Manuel José; Huertas Forero, Isaac; Orjuela Castro, Javier Arturo (Ingeniería, 2014)
This paper describes a mixed integer linear programming model for structuring and integrating strategic decisions and tactics, related to the production of biofuel biodiesel from African palm in Colombia. The model considers four regions (North, Central, Eastern and South - West), in order to coordinate a structured way fl ow of resources between the links in the chain starting with “harvesting” going through the middle steps of “extraction” and “conversion” until the fi nal step “mixture “, which are involved in the supply network. The goal of the model is to determine a distribution plan of palm, oil, biodiesel and diesel throughout the chain, along with a production and inventory plan, and a capacity increase plan for biorefi neries in a way that minimizes the total cost of the production chain over a predefi ned planning horizon. The application of the model results in a projection to the year 2043 showing the behavior of the chain, specifi cally soil requirements for such production levels.